Viajeros de tierras inconcebibles (2020)
First of all, to start an attempt to understand this issue, it must be very clear that we must separate the logic that we all normally use in the thoughts that we cover day by day, it is something that in this case is called conscious logic ; This logic will not be able to be used since everything has been tried to do from its counterpart, the unconscious logic, resulting for you as a spectator who makes use of your conscience a look at something that is probably not find meaning, that is to say something absurd. And it is that there are so many ways of approaching this issue, such as mental illnesses, or the dreamlike part of the mind that is responsible for creating dreams, that in one way or another they become an abstraction of what is collected in our conscious part, combining it with everything unexplored and extensive...